Antecedents of Facebook e-purchasing site and social CRM: a structural equation modeling from the customers’ perspectives - Anumudu, Chinedu Eugenia; Ogbomeh, Felix Chuks; Yasin, Megat Al Imran (Taylor's College, 2022)
Social Customer Relationship Management (Social CRM) is gaining ground globally, especially in this era that demands cashless transactions for promoting social commerce and reducing the spread of COVID-19. However, in some emerging nations like Nigeria, Social CRM via Facebook from the customer's perspective has not been researched widely. Therefore, this study aims to evaluate the antecedents of Facebook e-purchasing site and Social CRM from the perspective of customers. To realise the purpose of this study, we explored the Technology Acceptance Model (TAM) via a quantitative approach because of the descriptive and inferential requirements. Statistical Package for the Social Sciences (SPSS), and Structural Equation Modeling (SEM-AMOS) were employed to analyse the effects and mediation mechanisms. We found that the perceived information usefulness of Facebook purchasing sites does not significantly influence Social CRM while perceived site trustworthiness significantly influences Social CRM. Our findings further demonstrate that the perceived ease of use mediates the relationships between information usefulness and trustworthiness with Social CRM. However, the perceived site ease of use mediation mechanism on site information usefulness with Social CRM has a full mediation effect on Social CRM. We therefore, encourage Nigerian malls and other emerging countries' malls to consider making their Facebook e-purchasing sites simple for customers and potential buyers to boost Social CRM and promote social commerce. Our study further proffers insights to factors that can boost Social CRM and social commerce on Facebook and other social media platforms.